Development of a COBIT 5 EDM Domain–Based IT Governance Audit Website for Evaluating Maturity Level - Harahap, Risna Ariyasari; Alfiannur, Muhammad Rama; Akbar, Suraya; Rosdayanti (INSTALL: Information System and Technology Journal, 2025)
Digital transformation requires organizations to ensure that information technology governance aligns with strategic objectives and is capable of delivering measurable value. This study aims to develop an information technology governance audit website based on the COBIT 5 framework, specifically within the Evaluate, Direct, and Monitor (EDM) domain, as an instrument for evaluating maturity levels. The method used is Research and Development (R&D) with an Agile approach, encompassing the stages of exploration, design, development, and system evaluation. The system is developed using ReactJS on the frontend, Laravel with a REST API on the backend, and MySQL as the database. The website provides features such as role-based user management, EDM01–EDM05 assessment instruments, maturity level calculation on a scale of 0–5, gap analysis, dashboard visualization, and audit report export in PDF format. The results of Black Box Testing and User Acceptance Testing indicate that the system functions according to requirements and is capable of producing structured, integrated, and well-documented maturity level evaluations. This website is expected to improve the efficiency, transparency, and accuracy of IT governance audit processes in supporting organizational strategic decision-making.